Etika Al-Ghazālian dan Titik Temunya dengan Etika Kantian - R.F. Bhanu Viktorahadi (FOCUS, 2022)
With his immense intellectual stature and his encyclopaedic knowledge, al-Ghazâli has influenced Islamic thought and defined its practice for nearly nine centuries. Like many legal experts and philosophers, al-Ghazâli divides the universe into the transient world and the eternal hereafter. This world, or temporary existence, is subject to the will of God. It is not governed by a set of scientific laws, but is maintained, governed and driven by the direct and continual intervention of God (rejection of causality). God is not only the creator of the universe and of its attributes and laws (or the cause of existence). He is also the cause of every event in the world, great and small, past, present and future. As a Sufi, al-Ghazâli does have a theory of ethic as a part of his tasawuf discipline. Some experts come to consider al-Ghazâli as a Sufi figure, some other also goes to classify him as a prominent figure of philosophy. This is understandable actually, because from the books he wrote all indicates his interest on both tasawuf as well as philosophy. By considering his books Maqâshid al-Falâsifah or Tahâfut al-Falâsifah, or through his Mi’yâr al’Ilm, one would consider him as a true philosopher. But one might also comes to conclude him as a real Sufi or a true mystic simply by looking at his master piece works such as Ihyâ al-Ulûm al-Dîn, or Kitab al-Arbâ’in dan al-Munqidz min al-Dhalâl.